Denrobium moniliforme (L.) Sw. (Orchidaceae) - a new occurrence species for the flora of Vietnam - Huyen, Duong Duc (Academia Journal of Biology, 2014)
Dendrobium Sw. is the biggest genus of Orchidaceae in Vietnam. According to D. D. Huyen, this genus consists of 101 species. During period of four years (2005-2008), some expeditions have been organized in Hoang Lien National Park. A new occurrence species of genus Dendrobium (Orchidaceae) for Flora of Vietnam has been found in Sa Pa. Thus the genus Dendrobium in Vietnam consists of 102 species so far. Dendrobium moniliforme (L.) Sw. characterized by stem erect, narrowly cylindrical, with many nodes; internodes 2-4 cm; leaves 7-10 in two rows, lanceolate or oblong, 5-7 ´ 0.8-1 cm, apex obtuse and slightly unequally 2-lobed; racemes with 2-4 flowers; flowers 2.6-3.2 cm in diam., mentum conical, 0.4-0.5 cm; pedicel and ovary 1-1.9 cm, slender; sepals and petals similar, ovate-oblong or ovate-lanceolate, apex obtuse, white green or white tinged; sepals 1,2-1.6 ´ 0.4-0.6 cm, petals 1-1.4 ´ 0.5-0.8 cm; labellum pale yellowish green, or greenish white, 3-lobed, lateral lobes erect, suborbicular, clasping column; three keels with densely pubescent from base to an elliptic callus in middle of lip; a yellow green spot nearby callus. Flowered in March-May. Distribute in Laocai province (Sapa district), epiphyte in evergreen forest, 1000-1700 m alt. Studied specimens: Huyen 474 & 516 (HN). Author acknowledges the SBG Botanical Research Fellowship for help in his work of research genus Dendrobium Sw. in Vietnam.